The Church on the Hill in Schäßburg/Sighişoara. A Jewel of Architecture and Art-History on a Marginal Spiritual-Liturgical Existence - Fröhlich, Hans Bruno (Review of ecumenical studies, 2021)
The Evangelical Church C. A. in Romania has an impressive treasure trove of churches of cultural and art-historical value in Transylvania. One of the most important sacred buildings is the Church on the Hill in Schäßburg/Sighisoara. But although it is a liturgically important space, it has served other purposes over and over again in the course of history. The fact that the Evangelical community became very small after 1989 brought with it the challenge of using this place of worship adequately. In the last few decades - with the inclusion of the old town of Schäßburg on the list of UNESCO as a World Heritage Site - the Church on the Hill has become a tourist magnet. Culture lovers can listen to contemplative organ concerts. Due to the epidemiological situation, it now serves more and more liturgical purposes.